VIRTUAL REALITY IN PRODUCTION LAYOUT DESIGNING - Plinta, Dariusz; Kłaptocz, Karolina (Applied Computer Science, 2021)
Information technologies allow for improving production systems functioning especially thanks to a possibility of solving complex production problems in a very short time. The production system designing is increasingly based on virtual reality, and more specifically on the concept of a digital factory. It enables to create virtual models of real objects and use them for visualization of products and manufacturing processes. The presented examples of new information technologies, which are used in production practice, are the main object of this paper.